Key strategic issues pharmaceutical industry of SCM: A systematic literature review - Erick Fernando; Meyliana Meyliana; Harco Leslie Hendric Spits Warnars; Edi Abdurachman (Institute of Advanced Engineering and Science, 2020)
In this global era, making the competition in the pharmaceutical industry is very treacly. Implementation Supply chain management is the process of planning and managing all sourcing, procurement, distribution activities to increase value to customers and interested companies. Pharmaceutical companies are one that has a very complex supply chain. In this article will discuss the main issues that can improve industry strategic. This research is done by the systematic approach of literature to find things related to research. This study used 64 articles from search results. The results of this search are key issues in the pharmaceutical industry such as product and process development, capacity planning, factory and network design, e-business and IT applications, inventory management, outsourcing and reverse logistics, lean manufacturing, performance measures, people, and information technology. All of these findings are issues that improve the performance of supply chain management in the pharmaceutical industry.